2008
DOI: 10.1093/aje/kwn060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on Incident Hypertension and Diabetes in Chinese Asians, American Whites, and American Blacks: The People's Republic of China Study and the Atherosclerosis Risk in Communities Study

Abstract: Researchers have hypothesized that the impact of body mass index on chronic disease may be greater in Asians than in Whites; however, most studies are cross-sectional and have no White comparison group. The authors compared the associations with body mass index in Chinese Asians (n = 5,980), American Whites (n = 10,776), and American Blacks (n = 3,582) using prospective data from the People's Republic of China Study (1983-1994) and the Atherosclerosis Risk in Communities Study (1987-1998). Slopes of risk diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 27 publications
(28 reference statements)
6
52
0
2
Order By: Relevance
“…Our findings are compatible with those of many previous studies across various cohorts reporting that being overweight/obese increases the risk of developing hypertension (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The biological mechanisms involved in the development of hypertension associated with hyperadiposity have not been fully elucidated.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings are compatible with those of many previous studies across various cohorts reporting that being overweight/obese increases the risk of developing hypertension (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The biological mechanisms involved in the development of hypertension associated with hyperadiposity have not been fully elucidated.…”
Section: Discussionsupporting
confidence: 86%
“…25.0 kg/m 2 (5); this proportion continues to increase. Previous studies have indicated that being overweight/obese (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) increases the risk of hypertension in general.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Interestingly, some studies have found the opposite to be true, where the association of BMI with BP may be stronger in the Chinese-Asian population than in non-Asian populations. 12,13 It should be noted that these studies draw data from adults in mainland China, and therefore may not be analogous to the Asian-American population.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been estimated that the absolute genetic variances for BMI and weight are greater in Europeans than in East Asians, according to an adolescent twin study [2]. From an epidemiological viewpoint, moreover, it has been hypothesised that the overall impact of obesity on type 2 diabetes is greater in Asians than in Europeans [21]. Accordingly, it is of interest to compare the genetic associations between populations of European descent and Japanese populations.…”
Section: Introductionmentioning
confidence: 99%